2013
DOI: 10.1111/ajt.12276
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Pediatric Living Donor Liver Transplantation in Japan: An Analysis of More Than 2200 Cases Listed in the Registry of the Japanese Liver Transplantation Society

Abstract: The Japanese Liver Transplantation Society (JLTS) was established in 1980 in order to characterize and follow trends in patient characteristics and graft survival among all liver transplant patients in Japan. This study analyzed the comprehensive factors that may influence the outcomes of pediatric patients who undergo living donor liver transplantation (LDLT) by evaluating the largest cohort in the world. Between November 1989 and December 2010, 2224 pediatric patients underwent LDLT in Japan. There were 998 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
109
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 27 publications
9
109
2
2
Order By: Relevance
“…The LDLT survival rates have been similar to survival rates in DDLT recipients, for both adult and pediatric populations, 8,9,[14][15][16][17] with similar 1-, 3-, and 5 year survival rates compared to United States data in both LDLT and DDLT (Table 5). The most important factor affecting recipient outcome is recipient PELD/MELD score at the time of LT.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The LDLT survival rates have been similar to survival rates in DDLT recipients, for both adult and pediatric populations, 8,9,[14][15][16][17] with similar 1-, 3-, and 5 year survival rates compared to United States data in both LDLT and DDLT (Table 5). The most important factor affecting recipient outcome is recipient PELD/MELD score at the time of LT.…”
Section: Discussionmentioning
confidence: 72%
“…5,7 The primary cause of liver failure in our pediatric recipients was biliary atresia (30.4%) ( Table 1), which is similar to other regions in the world. 5,[7][8][9][10] In the early days of transplant, deceased donors were the only donor resource. With time, due to the growing gap between the number of available deceased donors and patients requiring LT, the transplant community developed new donor resources, resulting in use of split livers, expandedcriteria donors, donation after circulatory death (DCD), and living donors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they reported that graft liver dysfunction was the most useful independent predictor of a nadir of platelet counts after LT, although various mechanisms of thrombocytopenia were proposed. Following this report, two additional studies [22,23] confirmed that severe thrombocytopenia after LT was associated with graft loss or a poor patient outcome. However, the precise mechanisms by which post-transplant thrombocytopenia occurs and its relationship with graft dysfunction remain unclear.…”
Section: Thrombocytopenia and Patient Outcomesmentioning
confidence: 58%
“…8,9 Most grafts were obtained from living donors. A narrow organ donor pool is the most common problem that limits transplant in our country and around the world.…”
Section: Discussionmentioning
confidence: 99%